GENESIS MATERNITY BIRTH’S PREMATURE RUPTURE OF MEMBERANE (PROM) AT RSUP dr. SOERADJI TIRTONEGORO KLATEN - Erma Puji Astuti; Dwi Retno P; Suroso . (STIKES DUTAGAMA KLATEN, 2013)
Background: Premature Rupture Of Membranes (PROM) is a spontaneous rupture of membranes that occurs at any age in pregnancy before labor starts. PROM is the complication of premature pregnancy and the occurrence of chorioamnionitis infection to sepsis. The high incidence of PROM at dr. Soeradji Tirtonegoro Klaten on April 25 - May 31, 2013 amounted to 12.94% of all deliveries, with the causes including infection of membranes or cervical / vaginal, incompetent cervix, malposition, preterm pregnancy, cefalopelvik dispropotion (CPD), gemeli, polyhydramnios, vaginal trauma. Purpose: The purpose of this study was to determine the incidence of PROM at dr Soeradji Tirtonegoro Klaten, especially with maternal characteristics and causes of the PROM. Methods: The study used a descriptive method and research techniques that are kauntitatif. Sampling using sampling saturated, so that all women giving birth with the PROM at dr Soeradji Tirtonegoro Klaten on April 25 - May 31, 2013 as the sample of 55 women giving birth with the PROM. Results: Genesis PROM at dr. Soeradji Tirtonegoro Klaten on April 25 - 31 May 2013 as many as 55 (12.94%) with the characteristics of the respondents, aged 20-35 years were 43 (89.19%), in women who are not working as many as 46 (83.64%) , with a gestational age of 37-42 weeks, 47 (85.45%) and primigravida by 28 (50.9%). Cause of PROM incident at dr. Soeradji Tirtonegoro Klaten is vaginal trauma 12 (21.82%), cervical incompetence by 8 (14.55%), preterm pregnancies by 8 (14.55%), polyhydramnios 8 (14.55%), malposition as 6 (10.91%), infection of the membranes or cervical / vaginal 3 (5.45%), CPD 2 (3.64%), gemelli 1 (1.82%).Conclusion: The biggest cause of the incident PROM at dr. Soeradji Tirtonegoro Klaten on 25 April to 31 May 2013 were due to trauma vaginal intercourse (21.82%) and the smallest is the cause Gemelli (1.82%).